2014
DOI: 10.1108/scm-07-2013-0225
|View full text |Cite
|
Sign up to set email alerts
|

Integrated green supply chain management and operational performance

Abstract: Purpose – The purpose of this paper is to extend previous green supply chain management (GSCM) research by developing and empirically testing a conceptual framework that investigates the relationships between three dimensions of integrated green supply chain management (iGSCM) and multiple dimensions of operational performance. Design/methodology/approach – The study is based on survey data collected from 126 automotive manufacturers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
272
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(289 citation statements)
references
References 82 publications
12
272
1
4
Order By: Relevance
“…GSCM/PMS may comprise determining increases in waste elimination, recovery, recycling, and cost containment, as well as eliminating of additional dealing with time (comprising energy with raw materials). Yu, et al (2014) identified the relationship between green SCM and the dimensions of operational performance, and determined the measurements of SC performance. Mutingi, et al (2014) regard green SC as vital in improving the performance management system.…”
Section: Research Methodology With the Hypotheses Investigatedmentioning
confidence: 99%
“…GSCM/PMS may comprise determining increases in waste elimination, recovery, recycling, and cost containment, as well as eliminating of additional dealing with time (comprising energy with raw materials). Yu, et al (2014) identified the relationship between green SCM and the dimensions of operational performance, and determined the measurements of SC performance. Mutingi, et al (2014) regard green SC as vital in improving the performance management system.…”
Section: Research Methodology With the Hypotheses Investigatedmentioning
confidence: 99%
“…The findings of [53] further express that it is vital to consider supply-side and demand-side sustainabilityrelated collaboration as this could correspond to superior market and sustainability performance. From the inbound point of view, greening SCs could bring numerous benefits to a company such as cost reduction, and integrating suppliers in a participative decision making process could endorse environmental innovation [18]. Undoubtedly, upstream suppliers are instrumental in complementing SMCs of their downstream partners by providing sustainable inputs and facilitating prevention processes.…”
Section: Consequences Of Sustainability Management Capabilities On Pementioning
confidence: 99%
“…A remarkable progress has been made in the buyer-supplier relationship studies over the past decades. Further, despite some notable exceptions of green SCM [20,21,18], the development of SSCM literature has rather focused on a single entity than looking at the entire chain [22]. Previous studies called for more empirical studies to develop a better understanding of the capabilities of the first and second level suppliers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By implementing green customer and supplier integration, supply chain partners can work to solve environmental problems jointly [19][20][21]. They can combine external resources and internal resource endowments to generate benefits [1, 9,22].…”
Section: Theory Framework and Hypotheses Developmentmentioning
confidence: 99%